Investigating the impact of self-as-a-model interventions on children's self-regulation of learning, swimming performance, and thought processes. - Clark Larkin, Shannon. (University of Ottawa (Canada), 2005)
This study compared the impact of a self-modeling intervention (viewing oneself perform an adaptive behavior) and practice, a self-observation intervention (viewing oneself perform at current skill level) and practice or practice alone on children's self-regulation of learning, anxiety, swimming performance and thought processes. A mixed methodology approach was employed as both qualitative and quantitative data were obtained. The quantitative component operated within Zimmerman's (1989, 2000) theory of self-regulated learning, and as such four self-regulatory processes (self-efficacy, motivation, self-satisfaction, and goal setting), as well as anxiety and physical performance were examined. For the qualitative component, the current study employed a think-aloud protocol (Ericsson & Simon, 1996) with the goal of understanding the thought processes that unfolded when children viewed self-modeling and self-observation videos. Thirty-three children, between the ages of six and ten (mean age = 8.3 years), were randomly assigned to a self-modeling group, a self-observation group or a control group. The children participated in an eight-day swimming intervention program. The analyses with the quantitative data showed consistently that the self-modeling group obtained superior scores on the measures examining the self-regulatory processes and physical performance as compared to both the self-observation group and the control group, with these two groups performing similarly. These results provide support for the implementation of self-modeling interventions with children learning motor skills. The analysis of the verbal protocols clearly showed that the majority of the children's verbalizations were self-evaluative in both a positive (Descriptive Positive), and negative (Descriptive Negative) direction, as well as, being related to future skill improvement (Prescriptive). These finding are discussed in terms of how they relate to Bandura's social cognitive theory of modeling (1977, 1986, 1997). A comparison revealed very few differences between the self-modeling and the self-observation interventions, suggesting that children appear to be gaining information about their skill performance and what to do to improve their next performance attempts regardless of the type of intervention.
Keywords: Education, Physical.; Education, Educational Psychology.